Mafhūmu kalimātu “Qawlan Ma’rūfan dan Qawlan Sadīdan” fi Sūrati An-Nisā’ (Dirosah Ad-dalālah Al-qur’āniyah) - Mahmud Rifaannudin; Arina Sabilahaq (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The miracle of al-qurān in terms of language, al-qurān is the source of knowledge in this modern era. And al-qurān written in Arabic which contains meaning and science, including nahwu, ṣorof, dalālah and Balāghoh. Insaid I'lmu dalālah discusses about Ṣifah wal Mauṣūf, because the sentence is imperfect meaning if there are no words that characterize it. One sentence will be discussed in word of